Perception of Tourist towards the Potential Development of Tumpa Mountain Area as Integrated Ecotourism, Manado, North Sulawesi Province - Towoliu, Benny Irwan; Takaendengan, Mita Erdiaty (Graduate School, Universitas Brawijaya, 2015)
Tumpa is the name of mountain located at the northern part of the Manado City region which bordering The National Park of Bunaken. As a mountainous region with a height of ±623m (asl), it occupies a strategic position. In addition to being adjacent to the park, it is also part of uplands owned by the city of Manado. It serves as buffer zone (green belt) of water, horticultural and agricultural areas with mangrove coastal areas. Master Plan of Tourism Development Region in Manado City used as part of ecotourism products from mountain and forest, but so far there has been no in-depth study to assess the holistic perception of tourist in the development potency of the region as an integrated tourism in Tumpa Mountain area. This study was purposed to determine the tourist perception toward the potential development as integrated ecotourism. This research involved a qualitative research approach, described by using figures on the percentage. Fieldwork was used as a questionnaire survey. The analysis measurement using Likert Scale, scoring and analysis combined with the analysis of the interest rate (level of importance). This study result shows that the average respondent answered good with the score range between 3.5 until 4.2. It means the respondents have argued that every indicator; natural, social-cultural and infrastructure that exists in the region Tumpa Mount area is still in good condition. In the level of interest the respondents answered between 3.6 until 4.6 with category important. This means respondents expect that good environmental circumstances will be always maintained and linked with the development of tourist attraction which is very suitable to be developed as ecotourism. In conclusion, the indicators are considered good and important to be developed as an integrated ecotourism area. Keywords: Ecotourism, Integrated, Perception, Tourist, Tumpa Mount.